Unusual parapharyngeal lesion: aberrant thyroid gland - Feisal, T.K.; Prepageran, N.; Shahrizal, T.; Zulkiflee, A.B. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
An ectopic location of the thyroid gland usually occurs in the midline, starting anywhere from the tongue to the diaphragm. The occurrence of an ectopic thyroid gland in a non-midline site is extremely rare. We report a 32-year-old Malay woman with an aberrant thyroid gland presenting as a parapharyngeal lesion. She had a normally functioning thyroid gland. An ectopic thyroid should be considered as one of the differential diagnoses in the parapharyngeal mass.